ASSESSMENT OF HEAVY METAL POLLUTION STATUS IN THE MIDDLE SECTOR OF THE CITARUM RIVER - Wardhani, Eka; Raden Tina Rosmalina; Wulan, Diana Rahayuning; Fitri Dara; Lanang, Ragil Naga; Irmansyah, Athaya Zahrani (GEOMATE Journal, 2023)
River quality monitoring in Indonesia is still dominated by checking pollutant concentrations in river water. At the same time, sediment is also essential in providing an overview of the impact of various pollutants entering river water. Thus, it is necessary to review the heavy metal pollution status. Heavy metal pollution in river sediments can be problematic because it negatively impacts living organisms. Conversely, it also reveals the aquatic pollution by its depth layer. The critical parameters used in this study to determine the status of heavy metal pollution are Fe, Cd, Cr, Cu, Hg, Pb, and Zn at 40-60 cm depth. Sediment samples were taken from 3 locations in the Citarum River, Purwakarta Regency segment. The average measured concentration of heavy metals (mg/kg) in October 2022 was Fe: 527.425; Cd: n.d.; Cr: 0.214; Cu: 0.153; Hg: 0.012; Pb: 0.052; Zn: 1.671 and in November 2022 was Fe: 496.161; Cd: n.d.; Cr: 0.214; Cu: 0.164; Hg: 0.009; Pb: n.d.; Zn: 1.442. Contaminant Factor, Pollution Load Index, and Geoaccumulation Index calculations were used to determine the status of heavy metal pollution in water sediment in the Citarum River. The Contaminant Factor indicates that the sediment is low polluted, except for the parameter of Hg, which is categorized as moderately polluted. The Pollution Load Index indicates that heavy metal sediment in the Citarum Watershed is not polluted.